Physico-mechanical properties enhancement of pineapple leaf fiber (PALF) reinforced epoxy resin-based composites using guar gum (polysaccharide) filler: effects of gamma radiation. Issue 3 (3rd April 2022) - Hoque, Mohammad Bellal; Hannan, Md. Abdul; Mollah, M.Z.I.; Faruque, M.R.I.; Khan, Ruhul A.
Abstract : Pineapple leaf fiber (PALF) reinforced epoxy resin-based composites were fabricated by using hand lay-up technique. The fiber content in the composites was taken as 25% (w/w), then it was modified by inserting 5% guar gum (polysaccharide) filler. Results demonstrated a 6% and 9% increase of tensile strength (TS) and tensile modulus (TM), respectively, over that of virgin PALF-epoxy composites. But 7% reduced elongation at break (Eb%) was noticed in this study. Results also revealed a 6% increase of bending properties due to insertion of guar gum filler. The virgin PALF-epoxy composites and along with guar gum filler PALF-epoxy composites were treated by gamma radiation doses varied from 2.5 to 10 kGy. The results revealed improved tensile and bending properties at 5 and 7.5 kGy, respectively. Sheared composite samples were immersed into deionized water and it was observed that both composites with and without filler absorbed a lower amount of water. The fiber-matrix adhesion was obtained by scanning electron microscopy (SEM) on both composites. The functional groups of the composites were also determined by Fourier transform infrared spectroscopy (FT-IR) and evaluated in this study.